Constructor's key guide to PFI (Thomas Telford, 1998)
Providing an explanation of PFI, this work describes the process of how to obtain construction work in the public sector, and different opportunities PFI presents to different types of company. It is suitable for those construction contractors and consultants who do not have an expert knowledge of the complexities of PFI, but are affected by it.